Maintaining Socio-Cultural Values as a Media for Catholic Missions at Hati Kudus Tuhan Yesus Church in Ganjuran, Yogyakarta - Christian Maria Goreti; Yuliati Dewi; Agustinus Supriyono (Diponegoro University, 2020)
This study focusses on Hati Kudus Tuhan Yesus Church (Gereja Ganjuran) which built in the early 20th century by two brothers namely Dr. Joseph Ignaz Julius Maria Schmutzer and Ir. Julius Robert Anton Maria Schmutzer. These brothers' missions are different compared to other missions. They emphasize acculturation between Catholic values and Javanese culture. Explicitly, Catholic and Javanese culture are seen as different values. However, in its mission journey, the Schmutzer brothers were able to prove that those two values could be combined, matched, made interconnected with other values and they did not conflict with each other. Their Catholic mission was running well and achieving huge success. By using the historical method and emphasized archival studies, this study identifies the success factors of disseminating and maintaining local cultural values in spreading Catholic missions among Ganjuran Parish. This article answers that strong and maintained acculturation in Ganjuran is inseparable from preservation activities by the local community. One of the efforts is the Catholic community's ability to survive during a transition period. Besides, the mission has conducted a development in economics, education, and health. So, it is not surprising, if Ganjuran Church becomes one of the monuments that symbolize the Catholic mission's success conducted by Dutch people.